Sintesis Dan Karakterisasi Sifat Optik Polimer Film PVA-TCA-MB - Jannatin `Ardhuha; Ni Nyoman Sri Putu Verawati; Muhammad Taufik; Syahrial Ayub (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
Polyvinyl alcohol (PVA) based film polymers that contain trichloroacetic acid (TCA) and methylene blue (MB) dye has been synthesized. The synthesis aimed to obtain material that can be applied as film dosimeter. Six PVA-TCA-MB thin film samples have been synthsized by varying PVA grades and TCA composition. Characterization of optical property of the resulted polymer was undertaken by measuring samples absorption within wavelength range of 200 nm to 700 nm.ÃÂ  Absorption spectrum of samples showed an optimum between 547-644 nm that corresponds to purple colour and characteristic to MB absoption. Further analysis showed the influence of TCA concentration and storage periode of the polymer. Optimization of syntesis by evaluating synthesis condition, heating and storage time is yet to be done in order to obtain polymer that can be used as dosimeter with reproducible optical property.